3D Animation Design 'Busker City' Using Blender 2.83 Software - Mohamad Axel Putra Hadiningrat; Naufal Ahmad; Nenden Suryamanah Annisa (Cinematology: Journal Anthology of Film and Television Studies, 2023)
Busking is one of the impacts of urbanization caused by the condition that there are more jobs in cities than in villages. The existential of buskers in public places has a bad image for some people. In this design, the author is interested in making a visualization of Busker City in the form of a short 3-dimensional animated video with a duration of 2 minutes. The purpose of this design is to design a 3D animation video for Busker City. This creation method consists of 3 stages; Pre-production, Production and Post-production. The results of this 3D animation design are in the form of a short video consisting of 5 segments: (1) Openning; (2) Busking Station; (3) Buskers Park; (4) Market; and (5) Closing. This 3D animation video can also be entertainment and add to the aesthetic experience for those who watch it, as well as provide information about the author's idea of the City of Buskers. The author suggests that in the process of making animated videos, it is better to use adequate devices, especially in doing animation or moving objects and rendering.